2016
DOI: 10.1016/j.jacc.2016.09.482
|View full text |Cite
|
Sign up to set email alerts
|

TCT-351 Coronary sinus reducer implantation for the treatment of chronic refractory angina: a single center experience

Abstract: BACKGROUND Left main coronary artery (LMCA) disease treatment is traditionally surgical in most cases. Continuous improvement of devices and the emergence of drug-eluting stents (DES) has increased indications of percutaneous treatment in these high-risk lesions. The main objective of this study was to evaluate the efficacy and safety of percutaneous coronary intervention (PCI) with DES on LMCA at a 10 year follow-up. METHODSWe prospectively included 324 patients (69.53 AE 12.60 years, 73.4% male) with severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…Recently, in concordance with a previous sham‐controlled randomized trial, we have shown that Reducer implantation was associated with reduction in angina, improvement in quality of life and functional capacity of patients with refractory angina . There is initial evidence that the observed clinical benefit may be related to Reducer's effect on the improved myocardial perfusion .…”
Section: Introductionsupporting
confidence: 80%
“…Recently, in concordance with a previous sham‐controlled randomized trial, we have shown that Reducer implantation was associated with reduction in angina, improvement in quality of life and functional capacity of patients with refractory angina . There is initial evidence that the observed clinical benefit may be related to Reducer's effect on the improved myocardial perfusion .…”
Section: Introductionsupporting
confidence: 80%
“…Following the initial promising results, CS Reducer might represent a therapeutic option for refractory angina with a consequent increase of the implantation procedures. Knowing how to manage complications that may arise, can improve patients' outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Following the initial promising results, 5 The balloon catheter with the pre-mounted scaffold was advanced to reach the landing zone and the Reducer was deployed by inflating at 4 atm (A). Device dislodgement in the right atrium, following the retrieval of the balloon (B).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations